Birth outcomes after prenatal exposure to antiepileptic drugs—A population‐based study. Issue 11 (17th September 2014) - Kilic, Demet; Pedersen, Henrik; Kjaersgaard, Maiken Ina Siegismund; Parner, Erik Thorlund; Vestergaard, Mogens; Sørensen, Merete Juul; Olsen, Jørn; Bech, Bodil Hammer; Christensen, Jakob; Pedersen, Lars Henning
Summary Objective We studied the potential impact of antiepileptic drugs (AEDs) on fetal growth and gestational age at birth. Methods In the Danish Medical Birth Registry, we identified all pregnancies with birth outcomes from 1997 to 2008 and linked with data from the Danish National Prescription Register. We used binomial regression to study preterm birth (<37 weeks), low birth weight (<2, 500 g), and small for gestational age (SGA), adjusted for potential confounding factors including maternal age, smoking, substance abuse, cohabitation, income, education, and parity. Results We identified 679, 762 singletons, and 2, 928 (0.4%) of these had been exposed to AEDs. Exposure to AEDs was associated with a risk of preterm birth (adjusted risk ratio (aRR) 1.32; 95% confidence interval [CI] 1.16–1.50) when compared to unexposed children. However, when stratifying on maternal epilepsy, there was no association between AED exposure and preterm birth in offspring of women with epilepsy (aRR 1.00; 95% CI 0.82–1.21), whereas there was a risk associated with AED exposure in offspring of women without epilepsy (aRR 1.56; 95% CI 1.27–1.92). AED exposure was associated with a risk of being born with low birth weight (aRR 1.40; 95% CI 1.22–1.60) both for children born of women with epilepsy (aRR 1.32; 95% CI 1.06–1.63) and children born of women without epilepsy (aRR 1.61; 95% CI 1.28–2.02). The risk of being born SGA associated with AED exposure (aRR 1.21; 95% CI 1.10–1.34) was found both in offspring of women with epilepsy (aRR 1.19; 95% CI 1.02–1.37) and without epilepsy (aRR 1.21; 95% CI 1.01–1.45). Significance Prenatal AED exposure was associated with low birth weight and risk of being born SGA, but only with preterm birth among women without epilepsy.